2004
DOI: 10.1073/pnas.0400605101
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long-term treatment with low doses of the LHRH antagonist Cetrorelix on pituitary receptors for LHRH and gonadal axis in male and female rats

Abstract: Our previous studies showed that treatment of female rats with large doses of Cetrorelix, an antagonist of luteinizing hormonereleasing hormone (LHRH), reduces levels of serum LH, estradiol, progesterone, and the concentration of pituitary LHRH receptors (LHRH-Rs) and their mRNA expression. Serum LH and testosterone levels and pituitary LHRH-R in male rats are also decreased by high doses of Cetrorelix. This approach can be used for therapy of sex hormone-dependent cancers. However, in conditions where an inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 43 publications
2
30
0
Order By: Relevance
“…These results suggest an advantage over agonists in clinical conditions where a partial pituitary gonadal inhibition is desired [5, 11, 12]. In a recent study, Mardesic et al [14] showed in postmenarchal young women with hematological malignancies a rapid suppression of the pituitary-gonadal axis by combining of GnRH agonist and GnRH antagonist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest an advantage over agonists in clinical conditions where a partial pituitary gonadal inhibition is desired [5, 11, 12]. In a recent study, Mardesic et al [14] showed in postmenarchal young women with hematological malignancies a rapid suppression of the pituitary-gonadal axis by combining of GnRH agonist and GnRH antagonist.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple injections of these long-acting GnRH agonists over a period of time are necessary to forestall reactivation of the gonadotropin and gonadal steroid hormone secretion which reactivate soon after GnRH agonist treatment is discontinued [6]. GnRH antagonists offer theoretical advantages in treating precocious puberty, especially if an immediate suppression of gonadotropins is desired [5], but there are still no clinical data showing that GnRH antagonists are superior in treating precocious puberty compared to agonists in humans.However, experiments with rats indicate strong potential for the development and testing of long-acting depot preparations of GnRH antagonists (available for experiment use only) in treating precocious puberty, showing an immediate suppression of gonadotropin secretion by GnRH antagonist treatment [11]. Recently we were able to show in peripubertal female rats that a combination of antagonist and agonist could prevent the agonist ‘flare-up’, if the first injections of both were administered concurrently, while a sequential antagonist followed by agonist treatment was not effective [12], leading to the concurrent methodology used in this study.…”
Section: Introductionmentioning
confidence: 99%
“…injected into 60-64-dayold rats at 0.4 mg/day for 4 days as previously described. 33 T levels Figure 4 TVS167 administration modulates in vivo T production. (a) Testes dissected from adult Sprague-Dawley rats were cultured in media supplemented with or without TVG167 or TVS167 and/or hCG (120 minutes).…”
Section: The In Vivo Induction Of T By Tvs167 Is Lh-independentmentioning
confidence: 99%
“…There is no doubt that potent partial agonists may be useful in clinical practice, since they may provoke significant suppression of the hypothalamic-gonadotroph axis and allow endogenous oestrogen to remain at the level needed for maintenance of bone density and prevention of symptoms of oestrogen deficiency. For example, Horvath et al (2004) have approached this challenge using low doses of the GnRH antagonist, cetrorelix. Their results suggest that cetrorelix in low doses induces only a partial pituitary-gonadal inhibition and might be indicated for …”
Section: Discussionmentioning
confidence: 99%